Imagining Personal Data Experiences of Self-Tracking - Fors, Vaike (Taylor & Francis, 2019)
Digital self-tracking devices and data have become normal elements of everyday life. Imagining Personal Data examines the implications of the rise of body monitoring and digital self-tracking for how we inhabit, experience and imagine our everyday worlds and futures. Through a focus on how it feels to live in environments where data is emergent, present and characterized by a sense of uncertainty, the authors argue for a new interdisciplinary approach to understanding the implications of self-tracking, which attends to its past, present and possible future. Building on social science approaches, the book accounts for the concerns of scholars working in design, philosophy and human-computer interaction. It problematizes the body and senses in relation to data and tracking devices, presents an accessible analytical account of the sensory and affective experiences of self-tracking, and questions the status of big data. In doing so it proposes an agenda for future research and design that puts people at its centre.